PENERAPAN MODEL READ, ANSWER, DISCUSS, EXPLAIN, CREATE (RADEC) TERHADAP KEMAMPUAN BERPIKIR KREATIF SISWA PADA PEMBELAJARAN IPA DI KELAS V SD - Ani Nurjannah; Maharani Oktavia; Puji Ayurachmawati (STKIP Subang, 2023)
The problem that occurs from this study is the lack of students' creative thinking skills in science learning caused by the application of science material that still uses conventional models and questions and answers. The purpose of this study was to determine the effect of the application of the RADEC model on students' creative thinking skills in science learning class V SD N 88 Palembang. The research method used is the experimental method with a pretest-posttest control group design. The subjects of this study were students in grades V1 and V2 of SD N 88 Palembang, totaling 61 students. Methods of data collection using tests and documentation. The test instrument is in the form of essay questions totaling 10 questions to measure students' creative thinking abilities. The data analysis technique uses the Independent Sample T-test. The results showed that the application of the RADEC model could improve elementary students' creative thinking skills in science material which could be seen from the results of the hypothesis test (Independent Sample T-Test) in the form of a significance value in this study, namely 0.000 <0.05, which means Ho was rejected, Ha was accepted. Keywords: RADEC Model, Ability to think creatively